miR‐373 regulates inflammatory cytokine‐mediated chondrocyte proliferation in osteoarthritis by targeting the P2X7 receptor - Wei Zhang; Biao Zhong; Chi Zhang; Congfeng Luo; Yulin Zhan (FEBS Open Bio)
Inflammatory cytokines commonly initiate extreme changes in the synovium and cartilage microenvironment of osteoarthritis (OA) patients, which subsequently cause cellular dysfunction, especially in chondrocytes. It has been reported that induction of the purinergic P2X7 receptor (P2X7R) can regulate the expression of a variety of inflammatory factors, including interleukin (IL)‐6 and ‐8, leading to OA pathogenesis. However, knowledge of the mechanism of upregulation of P2X7R in OA is still incomplete, and its role in chondrocyte proliferation is also not clear. It was reported previously that the expression of P2X7R was controlled by certain microRNAs, and so we tested the expression of several microRNAs and found that microRNA‐373 (miR‐373) was downregulated in the chondrocytes from OA patients. Regarding the mechanism of action, miR‐373 inhibited chondrocyte proliferation by suppressing the expression of P2X7R, as well as inflammatory factors such as IL‐6 and IL‐8. Furthermore, the proliferative and pro‐inflammatory effects of miR‐373 on the chondrocytes could be suppressed by a P2X7R antagonist, further suggesting that miR‐373 mediates chondrocyte proliferation and inflammation by targeting P2X7R. Generally, our results suggest a novel method for OA treatment by targeting the miR‐373–P2X7R pathway.